Effects of icariin on the fracture healing in young and old rats and its mechanism - Xiaoyun Zhang; Yueping Chen; Chi Zhang; Xuan Zhang; Tian Xia; Jie Han; Shilei Song; Canhong Xu; Feng Chen (Taylor & Francis Group, 2021)
Context Icariin has attracted increasing attention because of its wide variety of pharmacological effects. Objective This study investigates whether icariin could promote fracture healing in young and old rats and its mechanisms. Materials and methods A Wistar rat model for the tibia fracture in relatively young and old rats, respectively, was established. The rats were divided into four groups: model group, L-icariin (50 mg/kg icariin), M-icariin (100 mg/kg icariin) and H-icariin (200 mg/kg icariin), and intragastric administration of icariin was performed for 10 days or 20 days. In addition, isolated and cultured rat bone mesenchymal stem cells (rBMSCs) from young and old rats were cultured with 5% and 20% of icariin-containing serum, respectively, then cell viability and alkaline phosphatase (ALP) activity were measured. Results Icariin administration induced the expression of Runx2, Osterix, BMP-2, p-Smad5 and osteocalcin secretion (young rats: model: 2.50 ± 0.71; L-icariin: 10.10 ± 1.55; M-icariin: 24.95 ± 2.19; H-icariin: 36.80 ± 2.26; old rats: model: 1.55 ± 0.49; L-icariin:6.55 ± 0.50; M-icariin: 15.00 ± 0.85; H-icariin:20.50 ± 2.27) at the fracture site, and increased the levels of bone formation markers (OC, BAP, NTX-1 and CTX-1) in a dose-dependent manner. In vitro, icariin treatment promoted rBMSC viability, increased ALP activity and the expression of BMP-2/Smad5/Runx2 pathway proteins. Discussion and conclusions Icariin may accelerate fracture healing by activating the BMP-2/Smad5/Runx2 pathway in relatively young and old rats. The research on the mechanism of icariin to promote fracture healing can provide a theoretical basis for the clinical application and promotion of icariin.